Effect of Cymbopogon citratus and Citral on Vascular Smooth Muscle of the Isolated Thoracic Rat Aorta. (22nd May 2012) - Devi, R. Chitra; Sim, S. M.; Ismail, R.
Abstract : Cymbopogon citratus has been shown to have antioxidant, antimicrobial, antispasmodic and chemo-protective properties. Citral, is the major constituent of C. citratus . This study investigated the effects of methanolic extracts of leaves (LE), stems (SE), and roots (RE) of C. citratus and citral on vascular smooth muscle and explored their possible mechanisms of action. The experiment was conducted using isolated tissue preparations, where citral, LE, SE, and RE were added separately into a tissue bath that contained aortic rings, which were pre-contracted with phenylephrine (PE). Citral, LE, and RE exhibited a dose-dependent relaxant effect on the PE-induced contractions. Citral appeared to partially act via NO as its vasorelaxant effect was attenuated by L-NAME. However, the effect of LE may involve prostacyclin as indomethacin reversed the relaxant effect of LE on the PE-induced contraction. Furthermore, citral, LE, and RE abolished the restoration of PE-induced contraction caused by the addition of increasing doses of calcium in both endothelium intact and denuded rings. These findings suggest that the relaxation effect of citral, LE, and RE is endothelium-independent and may be mainly by affecting the intracellular concentration of calcium. Citral may partially act through the NO pathway while a vasodilator prostaglandin may mediate the effect of LE.